The Importance of Work Discipline For Cooperative Services and Micro Enterprises In Banten Province - Hamdan Hamdan (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
The purpose of this research was to perceive The Influence of Organizational Culture and Physical Work Environment on Employee Work Discipline in the Office of Cooperatives and Micro, Small, and Medium Enterprises, Banten Province. The samples taken were 44 people. The number of employees in the office is 52 employees and the number of samples obtained was 52 respondents, and the sampling technique of this research was the Non Probability Sampling. The analysis tool used was IBM SPSS 25. The T-test results showed that organizational culture and physical work environment influence the employee work discipline, and the F-test result showed that organizational culture and physical work environment influence the employee work discipline